Family Structure is Associated with Mental Health and Attention Deficit (Hyperactivity) Disorders in Adolescents with Type 1 Diabetes - Baechle, Christina; Stahl-Pehe, Anna; Castillo, Katty; Holl, Reinhard W.; Rosenbauer, Joachim (Experimental and Clinical Endocrinology & Diabetes, 2022)
Objective To analyze the cross-sectional associations of family structure with mental health and attention deficit (hyperactivity) disorders (AD(H)D) in 11- to 17-year-old adolescents with early-onset type 1 diabetes participating in one of three baseline surveys as part of an ongoing cohort study.Methods Parents (n=1,631) completed the Strengths and Difficulties Questionnaire to screen for their child’s mental health and answered questions about their child’s diagnosis of AD(H)D. Associations between mental health or AD(H)D and family structure were analyzed using multivariable logistic regression analyses adjusted for various personal and diabetes-related variables.Results Compared to adolescents living with both parents, adolescents living with one parent and his/her partner had 2.35 (95% confidence interval 1.32; 4.21) higher odds of abnormal screening result and 2.08 (1.09; 3.95) higher odds of a borderline screening result while adolescents living with a single parent had 1.84 (1.07; 3.17)/1.08 (0.53; 2.21) higher odds of abnormal/borderline screening results. The odds ratios for diagnosed attention deficit (hyperactivity) disorder were 2.17 (0.98; 4.84) for adolescents living with one parent and his/her partner and 1.27 (0.54; 3.01) for those living with a single parent vs. both parents.Conclusions Our results indicate higher odds of mental health problems and AD(H)D in adolescents with type 1 diabetes who do not live with both parents; this finding was most pronounced in individuals living with one parent and his/her partner vs. both parents. Longitudinal studies are needed to verify our results and elucidate the underlying mechanisms.
Keywords: attention deficit hyperactivity disorder; ADHD; adolescence; psychology; T1D; childhood diabetes